A Delphi Study to Establish Research Priorities for Neuroscience Nursing. Issue 2 (10th April 2022) - Bautista, Cynthia; Hinkle, Janice L.; Alexander, Sheila; Hundt, Beth; Rhudy, Lori
ABSTRACT: BACKGROUND: Establishing research priorities is essential not only to support evidence-based nursing practice but also to direct research agendas for nursing organizations such as the American Association of Neuroscience Nursing. METHODS: A 6-member Research Agenda Task Force selected potential research priorities based on a literature search of neuroscience nursing research. Using a 2-round, modified Delphi methodology, electronic surveys were distributed to 53 neuroscience nursing experts to gain consensus on the research priorities for neuroscience nursing. Survey data included demographics, agreement with selected gaps in neuroscience nursing research, and impact of selected neuroscience nursing research topics on the field. RESULTS: Twenty-six of 53 experts (49% response rate) participated in round 1, and 30 of 53 experts (57% response rate) participated in round 2. In round 1, the Research Agenda Task Force members revised the list of gaps in neuroscience nursing research to include only the top 39 ranked topics with greater than or equal to 73% agreement, created a new category "Professional Practice Issues, " and added 1 additional topic. In round 2, 14 topics were ranked greater than or equal to 70% impactful and identified as the top neuroscience nursing research priorities. CONCLUSION: The results of this study served as an effort for creating research priorities and enhancing research collaboration that focuses on neuroscience nursing. Focusing on gaps in the literature and setting research priorities can ultimately improve patient outcomes. Neuroscience nursing research priorities can be used to inform, guide, and aid nurse scientists, educators, and providers, and to inform agencies that provide research and program funding.